The Egnatia Motorway and the Changes in Interregional Trade in Greece: An Ex Ante Assessment - Polyzos, Serafeim (European Spatial Research and Policy, 2010)
The Egnatia Motorway, located in the northern part of Greece, constitutes one of the most important, as well as ambitious, projects of the Trans-European Transport Networks programme (TETN) funded by the European Commission. It is expected to greatly influence the spatial economic relationships of several regions across the country. The motorway crosses all administrative regions of Northern Greece, and the expectations currently sustained by the public as regards its contribution to regional development are exceptionally great. As numerous empirical studies have already shown, the most important changes in regional economy induced by interregional transportation infrastructure are associated with trade flows between different regions. This paper analyses the major determinants of interregional trade in Greece and estimates the changes in interregional trade flows which the construction of the Egnatia Motorway is capable of generating.